2012
DOI: 10.2307/41703462
|View full text |Cite
|
Sign up to set email alerts
|

The Career Paths Less (or More) Traveled: A Sequence Analysis of IT Career Histories, Mobility Patterns, and Career Success

Abstract: The career paths less (or more) traveled : a sequence analysis of IT career histories, mobility patterns, and career success

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
118
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(150 citation statements)
references
References 82 publications
6
118
0
14
Order By: Relevance
“…Research has shown that work-related characteristics (e.g., job security, job fit, salary, autonomy, and organizational commitment) and social and environmental factors (e.g., professional socialization) are related to an employee's attitude and behavior concerning career changes. Some researchers forecast the emergence of boundaryless organizations in which individuals pursue ''boundaryless careers'' [21]. Thus, incorporating additional variables is likely to improve our understanding of ITPs' attitudes toward career commitment.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Research has shown that work-related characteristics (e.g., job security, job fit, salary, autonomy, and organizational commitment) and social and environmental factors (e.g., professional socialization) are related to an employee's attitude and behavior concerning career changes. Some researchers forecast the emergence of boundaryless organizations in which individuals pursue ''boundaryless careers'' [21]. Thus, incorporating additional variables is likely to improve our understanding of ITPs' attitudes toward career commitment.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…While career related movements can take many shapes and sizes, the literature informs us that these modes of movement can be classified as belonging to particular generic groups, or 'career paths'. In this paper, we follow Joseph, Boh, Ang and Slaughter's ( [18], p. 429) definition of career paths as "models or prototypes characterizing the career sequences of a group of individuals". Therefore, an individual's sequence of occupational movements become the observable manifestation of a particular career path.…”
Section: A Actors'occupational Development In Techical Innovation Symentioning
confidence: 98%
“…The sequence of movements between occupational positions that define an individual's career fittingly conjure a path along which the individual navigates professionally over time [1,17,10,18,3]. While career related movements can take many shapes and sizes, the literature informs us that these modes of movement can be classified as belonging to particular generic groups, or 'career paths'.…”
Section: A Actors'occupational Development In Techical Innovation Symentioning
confidence: 98%
See 2 more Smart Citations